Lip print pattern identification of Deutromalayan subrace using a modification of lip print formulation technique as forensic odontology application - Evirilia, Evirilia; Sam, Belly; Oscandar, Fahmi (Faculty of Dentistry Universitas Padjadjaran, 2015)
Introduction: Every individual has a different lip print pattern that facilitates personal identification. Every individual has the physical characteristics that are different from other individuals. The physical characteristics can be an identity for the individual. The purpose of this research was to investigate the lip print pattern among Deutromalayan subrace with a modification of lip print formulation technique. Methods: A descriptive research was conducted among 82 male and female students of 2008 batch students of Faculty of Dentistry Universitas Padjadjaran. The research was an observation of lip print from each subject in the digital view from the scanning of a lip seal. The observation was carried out on all parts of the fissure in the subject’s lip print. The data was then analysed to a lip print pattern formulation based on fingerprint formulation. Results: Lip print pattern of Deutromalayan subrace was different among each other and clarified in a formulation consisted of elements from the central fissure type, amount of median fissure, fissure tracing and all lip print type. Conclusion: Lip print pattern among Deutromalayan subrace was identified by modification of lip print formulation technique that was clarified on the formulation.